Penegakan Pajak Penghasilan (PPh) terhadap Perusahaan Asing di Indonesia: Kajian Yuridis Normatif - Irwan Triadi; Dimas Yanuarsyah; Evi Fitriani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to analyze law enforcement in collecting Income Tax (PPh) against foreign companies that have the status of foreign taxpayers in Indonesia in a normative legal manner. In a national economic situation that is experiencing a slowdown, optimizing tax revenues is an important strategy for the government to improve fiscal stability and economic growth. Foreign companies, both those running businesses through Permanent Establishments (PE) or without PE, are subject to tax obligations on income earned in Indonesia. Law enforcement in tax collection is carried out through a preventive approach such as the establishment of the Directorate of International Taxation, the implementation of the Automatic Exchange of Information (AEoI), and intensive supervision of Tax Returns (SPT). In addition, a repressive approach in the form of tax audits and tax collection is strictly carried out against domestic business entities that act as tax collectors for foreign companies. This study concludes that the combination of preventive and repressive efforts carried out by the Directorate General of Taxes is effective in ensuring compliance with foreign taxpayers and increasing state revenues from the international taxation sector.